(untitled) (Economic and Political Thought, 2015)
From 1970 to 2014, the Kingdom of Belgium introduced six reforms of the political system, which resulted in its change from a unitary state into a federal one and is undergoing evolution. The country divisions are based on linguistic and cultural differences. The Kingdom of Belgium is still a constitutional monarchy but it consists of three regions, three communities and four language regions. Each region and community elects its local parliament and the Federal Parliament at the federal level, which is composed of the House of Representatives and the Senate. The latest reform changed the principles of the functioning of the Senate: the number of senators was raised to 60 and they are appointed (nominated and co-opted). Belgium’s political scene reflects the historical conflict of interest between Dutch-speaking Flanders and French-speaking Wallonia. The New Flemish Alliance led by a charismatic politician and a republican Bert de Wever has been gaining importance since 2004. The party slogans call for maximum autonomy for Flanders and finally the creation of a confederation of Flanders and Wallonia, if the latter agreed. The N-VA reports spectacular successes in local and federal elections. The article aims to analyse the reasons of the present development of the situation in the Kingdom of Belgium and to outline the direction that dynamically developing Flanders determines for the country.